Social Cognitive Approach through Interactive Multimedia for Early Reading Learning - Indah Nurmahanani; Munir Munir; Yeti Mulyati; Andoyo Sastromiharjo (Universitas Muhammadiyah Purwokerto, 2021)
This study developed a learning model to improve students’ early reading skills in Indonesia. The model is based on social cognitive learning theory and is implemented using interactive multimedia. The research method uses Design-Based Research (DBR) and the subjects are 195 first and second graders of an elementary school in Bandung, West Java. The findings of the study show that social cognitive learning can be integrated and implemented through interactive multimedia and that interactive-multimedia-assisted social cognitive model (IMAS Model) can improve early reading skills. Students’ average early reading skill scores were measured using Early Grade Reading Assessment (EGRA) instrument before and after intervention to see the effectiveness of the model. Pre-test – post-test results comparison showed that students’ average early reading scores increased after learning using IMAS Model. Students’ average scores of reading letters, reading syllables, reading words, reading sentences, and reading comprehension skills at pre-test were 78.06, 67.06, 60.92, 55.21, and 44.95, respectively. These scores respectively increased to 92.71, 92.45, 88.58, 74.60, and 87.08 at post-test, indicating that IMAS Model is effective to increase early reading skills.